Comparative Study of Paradigm on Science: Holistic View by Frithjof Capra and Knowledge Formulation by Yuval Noah Harari - Santi, Selvia (Proceeding International Conference on Science and Engineering, 2019)
An paradigm of science, since the beginning of the formation of scientific formulation, it has always undergone a change, as well as Thomas Kuhn’s scientific revolution theory. The paradigm is always tested with new theories until finally the obsolete paradigm is no longer used or is still partially used. At first the mechanistic paradigm introduced by Isaac Newton has long been a basic reference. But then, this paradigm is tested by the many problems of science, especially physics that no longer cannot be solved with this paradigm. The paradigm problem is a long search process because the paradigm not only regulates the workings of science in the laboratory, but also determines the results that have a significant impact on humans. The process of finding new paradigm is being pursued by two figures to be discussed, Fritjhof Capra and Yuval Noah Harari. Both give more attention to the paradigm of modern science that is unable to answer new challenges. Capra provides a new paradigm solution which he calls a holistic paradigm that seeks to see reality as an integration with a series of inseparable life networks. Whereas Harari, through his two best-selling books, Homo Sapiens and Homo Deus, revealed the latest theories and discoveries in the fields of physics, chemistry, biology to art, from his description he produced a synthesis of paradigm changes in reformulating knowledge which has positive implications for human survival. The method that will be used is the comparative method, thus the thinking of both of them will be abstracted in their similarities and differences of thought. The purpose of this research is to explore the latest science paradigm process proposed by the two figures, Capra and Harari.